2006
DOI: 10.1111/j.2006.0030-1299.14487.x
|View full text |Cite
|
Sign up to set email alerts
|

What shapes amino acid and sugar composition in Mediterranean floral nectars?

Abstract: . What shapes amino acid and sugar composition in Mediterranean floral nectars? Á Oikos 115: 155 Á169.We studied the amino acid (AA) composition of the floral nectars of 73 plant species occurring in a phryganic (East Mediterranean garrigue) community and investigated whether AA and sugar composition is shaped by evolutionary (plant phylogeny), ecological (flowering time as a direct effect of summer drought) and coevolutionary (pollinator partnership) constraints. Our study utilised an extensive plant Ápollina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
158
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(170 citation statements)
references
References 53 publications
9
158
1
2
Order By: Relevance
“…Fine-scale spatial and temporal measurements, combined with floral and bud manipulations, revealed that elevated humidity levels are produced by evaporation and transpiration, two fundamental physical and physiological processes occurring naturally during anthesis. Nectar evaporation is a known source of postsecretory variation in nectar concentration and energetic content (22,23). Here we provide a proof of principle that elevated humidity levels produced by nectar evaporation could provide a condition-dependent indicator of profitability (in the presence of nectar, rather than its quality), to those flower-visiting animals capable of perceiving it.…”
Section: Discussionmentioning
confidence: 64%
“…Fine-scale spatial and temporal measurements, combined with floral and bud manipulations, revealed that elevated humidity levels are produced by evaporation and transpiration, two fundamental physical and physiological processes occurring naturally during anthesis. Nectar evaporation is a known source of postsecretory variation in nectar concentration and energetic content (22,23). Here we provide a proof of principle that elevated humidity levels produced by nectar evaporation could provide a condition-dependent indicator of profitability (in the presence of nectar, rather than its quality), to those flower-visiting animals capable of perceiving it.…”
Section: Discussionmentioning
confidence: 64%
“…fructose) ratio of 0.16]. When compared with the results obtained for other closely related plant species, a low proportion of sucrose, resulting in hexose-rich or hexose-dominant nectars seems a common feature of Apiaceae (Percival 1961;Langenberger and Davis 2002;Petanidou et al 2006). This feature is also found in other plants with shallow, bowl-shaped flowers and exposed nectaries, and may be an adaptation to prevent the rapid evaporation of nectar (Corbet 1978;Vezza et al 2006).…”
Section: Discussionmentioning
confidence: 94%
“…This expectation is not unreasonable, as the floral scents of populations of related plants often exhibit variation in subtle features such as differences in the concentration of the same odour compounds (Raguso et al 2003;, which result in small but perceivable differences (Wright et al , 2008. Furthermore, nectar rewards associated with floral scents also vary in quality (Petanidou et al 2006) and quantity (Herrera et al 2006) even in flowers produced by the same plant (Herrera et al 2006). Nectar is the currency of the interaction between plants and their pollinators: it costs plants to produce nectar ( Nepi & Stpiczynska 2008), and pollinators such as honeybees and bumblebees carefully attend to the nectar quality and to the probability of encountering food offered by flowers ( Waddington 2001;Cnaani et al 2006;Drezner-Levy & Shafir 2007;Shafir et al 2008).…”
Section: Introductionmentioning
confidence: 99%